Can memory and executive functions in patients with obsessive–compulsive disorder predict outcome of cognitive behavioural therapy?. (2nd April 2016) - Vandborg, Sanne Kjær; Hartmann, Tue Borst; Bennedsen, Birgit Egedal; Pedersen, Anders Degn; Thomsen, Per Hove
Abstract: Background : Most studies find that patients with obsessive–compulsive disorder (OCD) have impaired memory and executive functions. Cognitive behavioural therapy (CBT) is the recommended psychotherapeutic treatment of patients with OCD. We hypothesized that impairments in memory and executive functions would predict poor outcome of CBT. Aim : To investigate whether memory and executive functions in patients with OCD could predict outcome of CBT. Methods : We assessed 39 patients with OCD before CBT with neuropsychological tests of memory and executive functions, the Hamilton Depression Rating Scale, and the Global Assessment of Functioning Scale. Furthermore, we assessed severity of OCD symptoms before and after CBT using the Yale–Brown Obsessive Compulsive Scale. Results : There were no statistically significant differences between recovered (41%) and non-recovered patients (59%) on any neuropsychological test variables or on any baseline demographic variables. Furthermore, change in OCD symptoms was not predicted by neuropsychological test performances or baseline severity of OCD symptoms. The only statistically significant finding was that non-recovered patients had lower social functioning before CBT than recovered patients ( p = 0.018, d = 0.797). Conclusions : Memory and executive functions in patients with OCD could not predict outcome of CBT, but level of social functioning may be a predictor of CBT outcome. Some of the main clinical implications are that we cannot use memory and executive functions, or baseline severity of OCD symptoms to determine which patients should be offered CBT.